Acetylcarnitine Is Associated With Cardiovascular Disease Risk in Type 2 Diabetes Mellitus - Zhao, Shuo; Liu, Ming-Li; Huang, Bing; Zhao, Fu-Rong; Li, Ying; Cui, Xue-Ting; Lin, Rong (Frontiers in Endocrinology, 2021)
Objective: This study aimed to identify the association between specific short-chain acylcarnitines and cardiovascular disease (CVD) in type 2 diabetes mellitus (T2DM). Method: We retrieved 1,032 consecutive patients with T2DM who meet the inclusion and exclusion criteria from the same tertiary care center and extracted clinical information from electronic medical record from May 2015 to August 2016. A total of 356 T2DM patients with CVD and 676 T2DM patients without CVD was recruited. Venous blood samples were collected by finger puncture after 8 hours fasting and stored as dried blood spots. Restricted cubic spline (RCS) analysis nested in binary logistic regression was used to identify possible cut-off points and obtain odds ratios (ORs) and 95% confidence intervals (CI) of short-chain acylcarnitines for CVD risk in T2DM. Ryan-Holm step-down Bonferroni procedure was performed to adjust P values. Stepwise forward selection was performed to estimate the effects of acylcarnitines on CVD risk. Result: The levels of C2, C4, C6 were elevated and C5-OH was decreased in T2DM patients with CVD. Notably, only elevated C2 was still associated with increased CVD inT2DM after adjusting protentional confounders in multivariable model (OR: 1.558, 95%CI: 1.124-2.159, P-values: 0.008). Furthermore, the association was independent of previous adjusted demographic and clinical factors after stepwise forward selection (OR: 1.562, 95%CI: 1.132-2.154, P-values: 0.007). Conclusions: Elevated C2 was associated with increased CVD risk in T2DM.